The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1967
DOI: 10.1111/j.1476-5381.1967.tb02121.x
|View full text |Cite
|
Sign up to set email alerts
|

A COMPARATIVE STUDY OF THE NORADRENALINE‐DEPLETING AND SYMPATHETICBLOCKING ACTIONS OF GUANETHIDINE AND (—)‐β‐HYDROXYPHENETHYLGUANIDINE

Abstract: (-)-,f-Hydroxyphenethylguanidine is the most active of a series of aralkylguanidines studied for their ability to lower the noradrenaline content of sympathetically-innervated tissues. It is several times more potent in this respect than guanethidine, but, unlike guanethidine, it produces only weak impairment of sympathetic transmission. In this paper we have compared the mechanisms of noradrenaline depletion by guanethidine and (-)-,8-hydroxyphenethylguanidine, and studied the relationship between noradrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1972
1972
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Similarly, SK&F 24260 (Maxwell, Mull & Plummer, 1959;Maxwell, Plummer, Schneider, Povalski & Daniel, 1960) by interfering with the synthesis of noradrenaline (Abercrombie & Davies, 1963) or by otherwise depleting the local stores. Fielden & Green (1967) concluded that guanethidine also had a strong adrenergic neurone blocking action distinct from the depleting action. It has been suggested that a reduction in total peripheral resistance (by blocking the sympathetic nervous system) is the mechanism by which guanethidine lowers blood pressure (Chamberlain & Howard, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SK&F 24260 (Maxwell, Mull & Plummer, 1959;Maxwell, Plummer, Schneider, Povalski & Daniel, 1960) by interfering with the synthesis of noradrenaline (Abercrombie & Davies, 1963) or by otherwise depleting the local stores. Fielden & Green (1967) concluded that guanethidine also had a strong adrenergic neurone blocking action distinct from the depleting action. It has been suggested that a reduction in total peripheral resistance (by blocking the sympathetic nervous system) is the mechanism by which guanethidine lowers blood pressure (Chamberlain & Howard, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Guanethidine (0.02 mg/g bw) was injected once on day 0, followed by a single injection on day 3 (0.04 mg/g bw) to selectively deplete NA stores without destruction of nerve endings (early recovery, (20)). 6-OHDA (0.03 mg/g bw) was injected once on days 0 and 1 to selectively destroy NA containing nerve endings (late recovery).…”
Section: Neuro-pharmacological Manipulationsmentioning
confidence: 99%
“…In the current study, we therefore investigated whether alterations in adrenergic skin innervation or b-AR stimulation by neurotransmitters may stimulate telogen-anagen transformation of murine HFs in vivo. Using the C57BL/6 mouse model for hair research, the NAdepleting agent guanethidine was administered s.c. to transiently empty noradrenaline stores of cutaneous adrenergic nerve fiber endings (20); the neurotoxin 6-OHDA was applied s.c. to selectively destroy noradrenergic nerve fiber endings (15); and the b-AR agonist isoproterenol was studied to test the effect of b-AR stimulation (13).…”
mentioning
confidence: 99%
“…In contrast to guanacline, which does not reduce responses, the block of responses to electrical stimulation produced during guanethidine treatment could be due to the potent and specific adrenergic neurone blocking action of this drug, independent of noradrenaline depletion. This action has been well documented and reviewed (Boura & Green, 1965;Fielden & Green, 1967) and would result in a much-reduced release of noradrenaline. Although there are no published reports comparing the adrenergic neurone blocking potency of guanethidine and guanacline, the relative effect of these two drugs in acute experiments would indicate that guanacline was a much weaker adrenergic neurone blocking drug, that is, it would not block the release of noradrenaline as much as would guanethidine.…”
Section: Discussionmentioning
confidence: 98%
“…This action has been well documented and reviewed (Boura & Green, 1965;Fielden & Green, 1967) and would result in a much-reduced release of noradrenaline. Ambache & Zar (1971), that the motor response may be at least partly non-adrenergic.…”
Section: Endogenous Noradrenaline Contentmentioning
confidence: 99%